Fatal Anaphylaxis to Pork: A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Food allergy is a common cause of anaphylaxis, which affects up to 10% of young children and 2–3% of adults, and its prevalence appears to be increasing constantly; however the precise incidence of food-induced fatal anaphylaxis among people is unknown. In the case of anaphylactic shock death is likely to occur rapidly and without any warning in seemingly healthy subjects. The lack of reliable laboratory biomarkers and common standard definitions of signs and symptoms makes it difficult for clinicians to diagnose a suspected anaphylactic event. Furthermore at autopsy the findings might hint at the allergic reaction, but classic manifestations may not be appreciated thereby making postmortem diagnosis of anaphylaxis difficult. Here we report one such case of death due to anaphylaxis in a young women with childhood history of allergy to pork.
Keywords: Sudden death; Anaphylaxis; Food allergy; Pork; Serum trytase levels; IgE antibodies; Autopsy